Innovative Learning: Scientific Approach to Deepen Understanding of Marfu' Hadith - Suci Prihatiningtyas; ajeng purbaningrum; asiyah husna (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
This study examines the implementation of the Scientific Approach in enhancing students' understanding of Marfu' Hadith concept in MA Unggulan KH. A. Wahab Hasbullah. Pre-test and post-test results analysis reveals a significant improvement in students' comprehension after the adoption of the Scientific Approach. Initially, pre-test scores averaged 48.30, indicating limited understanding due to unfamiliarity with the material and difficulty in answering questions. However, post-test results showed a notable increase, with all students achieving an average score of 76.07. This substantial enhancement underscores the effectiveness of the Scientific Approach in deepening students' understanding of Marfu' Hadith. The findings highlight the importance of innovative teaching methodologies, such as the Scientific Approach, in promoting comprehensive comprehension of complex religious concepts among students, thus contributing to the advancement of education in Islamic studies.